Perlindungan Hukum Perempuan Dalam Politik: Tinjauan Fikh Siyasah - Dewi Ulfa Lailatul Fitria; Rona Merita (Universitas Pangeran Diponegoro Nganjuk, 2024)
Women have the right to participate in the political sphere, as guaranteed by the principles of equality and justice. This study examines the legal protection of women in politics from the perspective of fiqh siyasah, focusing on efforts to achieve gender justice in political policies and practices. Using a normative approach and textual analysis of fiqh sources, the research finds that fiqh siyasah offers flexibility to adapt women's roles in politics as long as Sharia principles are upheld. The study also highlights the importance of legal regulations supporting women's participation to avoid discrimination and ensure equal representation in political decision-making processes.